Motivasi Berlatih Pemain Silat Keluarga Silat Nasional Perisai Diri - Provinsi Bali - . Sukrianingsih; Eka N. Kencana; Tari Tastrawati (Jurnal Matematika, 2018)
Silat is a class of indigenous martial arts found in some countries in Southeast Asia such as Indonesia, Malaysia, Brunei, Singapore, and south of Thailand. In Indonesia, silat is organised by several silat organisations according to its style (aliran) or school (perguruan). This essay is aimed to study the motivation of playing silat and classify it into its motivational factors by applying confirmatory factor analysis. The data were collected by distributing self-administered questionnaire to 180 members of Perisai Diri at Bali Province, one silat school in Indonesia. Six factors were confirmed as motivational factors for playing silat. These factors, order decreasingly according to their variance explained, are Appreciation of Indigenous Culture, Personal Achievement, Self-Defence, Recreation, Health Maintenance, and Mental & Spiritual Building.